13C MRS reveals a small diurnal variation in the glycogen content of human thigh muscle. (16th April 2015) - Takahashi, Hideyuki; Kamei, Akiko; Osawa, Takuya; Kawahara, Takashi; Takizawa, Osamu; Maruyama, Katsuya
<x xml:space="preserve">Abstract</x> There is marked diurnal variation in the glycogen content of skeletal muscles of animals, but few studies have addressed such variations in human muscles. 13C MRS can be used to noninvasively measure the glycogen content of human skeletal muscle, but no study has explored the diurnal variations in this parameter. This study aimed to investigate whether a diurnal variation in glycogen content occurs in human muscles and, if so, to what extent it can be identified using 13C MRS. Six male volunteers were instructed to maintain their normal diet and not to perform strenuous exercise for at least 3 days before and during the experiment. Muscle glycogen and blood glucose concentrations were measured six times in 24 h under normal conditions in these subjects. The glycogen content in the thigh muscle was determined noninvasively by natural abundance 13C MRS using a clinical MR system at 3 T. Nutritional analysis revealed that the subjects' mean carbohydrate intake was 463 ± 137 g, being approximately 6.8 ± 2.4 g/kg body weight. The average sleeping time was 5.9 ± 1.0 h. The glycogen content in the thigh muscle at the starting point was 64.8 ± 20.6 mM. Although absolute and relative individual variations in muscle glycogen content were 7.0 ± 2.1 mM and 11.3 ± 4.6%, respectively, no significant difference in glycogen content was observed among the different time points. This study demonstrates that normal food intake (not fat and/or carbohydrate rich), sleep and other daily activities have a negligible influence on thigh muscle glycogen content, and that the diurnal variation of the glycogen content in human muscles is markedly smaller than that in animal muscles. Moreover, the present results also support the reproducibility and availability of 13C MRS for the evaluation of the glycogen content in human muscles. Copyright © 2015 John Wiley & Sons, Ltd.